Quality of life after coronary artery bypass graft surgery in the elderly - Apostolakis, Efstratios; Pistolas, Dimitrios; Papagiannaki, Vasileia; Diakomopoulou, Eleni; Patiraki, Elisabeth; Merkouris, Anastasios (My University, 2008)
Background The aim of this study is to explore the quality of life of elderly patients after coronary artery bypass graft (CABG) surgery. Methods The present study employed a pre–post test design. Sixty three elderly patients (≥ 65 years), operated in one big general hospital in Athens, were interviewed before, 4 months and 12 months after CABG with the MacNew Heart disease health-related quality of life questionnaire. Results The majority of the sample were male (N = 48, 76.2%), married (N = 49, 77.8%) and pensioners (N = 54, 61.7%). After the operation and before discharge 42 (66.6%) patients presented complications. One year after the operation, 45 (80.4%) patients experienced improvement and only 11 (19.6%) deterioration in their reported quality of life. Despite this postoperative improvement in all domains, a high percentage of patients (> 60%) continued to report exacerbation in questions related to self confidence and dependence to others indicating an overprotective environment. Approximately one in two patients reported signs of cognitive dysfunction during the postoperative period. Elderly patients knew very little about their disease, especially before the operation (mean = 2.03, SD = 0.69, R = 1–5). Educational level, presence of complications in the immediate postoperative period and reported angina were related to a poorer QoL. Conclusion A high proportion of the patients experienced improvement while a substantial number had exacerbations related to self confidence and dependence to others. An important step to improve this situation might be through the institution of a structured multi-disciplinary rehabilitation program with focus on emotional support, information giving and education to elderly CABG patients and their significant others.
Keywords: Coronary artery bypass graft; Quality of life; Elderly